Heavy metal pollution and risk assessment of tailings in one low-grade copper sulfide mine - Zhao, Pingping; Chen, Jinghe; Liu, Tianfu; Wang, Qiankun; Wu, Zengling; Liang, Shuqin (Frontiers in Environmental Science, 2023)
Analyzing the pollution level and ecological risk of heavy metals in tailings is a necessary step for conducting revegetation after a tailings pond’s closure. Herein, we determined the heavy metal pollution status and ecological risk in one low-grade copper sulfide tailings pond using chemical and mineralogical analysis, chemical extraction, and ecological risk assessment. The results showed that the low-grade copper sulfide tailings displayed a low pollution status and exhibited very low ecological risk. Among six heavy metals (Cu, Pb, Zn, As, Cr, and Cd), only Cu (53.7 mg/kg) slightly exceeded its standard value limit (50 mg/kg), and was the main pollutant in the tailings. Due to its high toxicity, As had the maximum contribution to the potential ecological risk in the tailings. Pb, Zn, Cr, and Cd in the tailings were practically of no pollution, and exhibited low or none potential ecological risk. In order to conduct revegetation in the tailings pond, more attention should be paid to the acidity change of tailings and its impact on the chemical activity and bioavailability of Cu and As. This research provides a theoretical basis for risk control of heavy metals and revegetation in the low-grade copper sulfide tailings pond.